The water footprint assessment of water supply treatment process (WSTP) - comparison between Semambu, Kuantan WSTP and Peramu, Pekan WSTP - Melissa, Madsahik (2017)
The competition of water needs is increasing as the numbers of population increases as well as the increase demand of clear water, and the effect of climate change. This phenomenal will induce water scarcity if no precautions are taken. Thus, the sustainability of our water resources is in jeopardy. An application of Life Cycle Assessment (LCA) has long been used to determine water sustainability. However, this application is limited to the impact of the products to the environment. In this study, Water Footprint (WF) approach was utilized to determine the sustainability of our water supply. The objectives of this study are to determine WF at Semambu, Kuantan Water Supply Treatment Process and Peramu, Pekan Water Supply Treatment Process (WSTP). Besides that, this study also to investigate the effect of population, land use and monsoonal changes to the WF accounting for both WSTP. Another than that, this finding also to compare the efficiency of different types of WSTP in terms of WF. The last but not least, is to predict the WF for both WSTP from year 2016 until 2020 by using Artificial Neural Network (ANN) which is an artificial intelligence application so that the effective ways can be taken to ensure the sustainability of water at the end of findings.